2020
DOI: 10.3389/fnagi.2020.596894
|View full text |Cite
|
Sign up to set email alerts
|

Early Dendritic Dystrophy in Human Brains With Primary Age-Related Tauopathy

Abstract: Dystrophic neurites (DNs) are found in many neurological conditions such as traumatic brain injury and age-related neurodegenerative diseases. In Alzheimer’s disease (AD) specifically, senile plaques containing silver-stained DNs were already described in the original literature defining this disease. These DNs could be both axonal and dendritic in origin, while axonal dystrophy relative to plaque formation has been more extensively studied. Here, we demonstrate an early occurrence of dendritic dystrophy in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…A total of 14 brains from donors aged above 65 years were included in the current study to study Shank3 IR in the cerebral and cerebellar sections. Among these brains from elderly individuals, seven cases were pathologically characteristic of PART ( Shi et al, 2020 ); one case showed tauopathy together with early Aβ lesion at Thal phase 1, with the remaining six cases had late-stage pTau (Braak Stage IV and above) and Aβ (Thal Phase 4 and above) burdens met the criteria for neuropathological diagnosis of AD according to the NIH guideline ( Table 1 ). On examination of cerebral sections from these cases, we noticed a trend of reduction and even loss of Shank3 immunoreactive neuronal somata in the associative and primary functional areas ( Figures 11A–D , as examples), in comparison with that seen in sections from the youth or adult cases ( Figures 1 , 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 14 brains from donors aged above 65 years were included in the current study to study Shank3 IR in the cerebral and cerebellar sections. Among these brains from elderly individuals, seven cases were pathologically characteristic of PART ( Shi et al, 2020 ); one case showed tauopathy together with early Aβ lesion at Thal phase 1, with the remaining six cases had late-stage pTau (Braak Stage IV and above) and Aβ (Thal Phase 4 and above) burdens met the criteria for neuropathological diagnosis of AD according to the NIH guideline ( Table 1 ). On examination of cerebral sections from these cases, we noticed a trend of reduction and even loss of Shank3 immunoreactive neuronal somata in the associative and primary functional areas ( Figures 11A–D , as examples), in comparison with that seen in sections from the youth or adult cases ( Figures 1 , 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the brains from the elderly cases (≥ 65 years) were commonly found to show a certain degree of Alzheimer-type Aβ and neurofibrillary tangle (NFT) pathologies according to the Thal Aβ and Braak NFT/pTau staging guidelines ( Braak and Braak, 1991 ; Thal et al, 2002 ; Braak et al, 2006 ; Montine et al, 2012 ; Table 1 ). A substantial number of the brains from the aged cases exhibited features of the so-called primary age-related tauopathy (PART), with Braak pTau stages I-IV in the absence of Aβ deposition ( Shi et al, 2020 ). The neuropathological characterization methodology was included in our recent studies ( Xu et al, 2019 ; Shi et al, 2020 ; Tu et al, 2020 ), therefore it is not detailed here (to avoid redundancy).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Rock2 expression resulted in lower dendritic spine density ( Henderson et al, 2019 ), whereas Rock inhibition increases the number of thin spines and filopodia, which would enhance synapse formation and neuronal plasticity ( Swanger et al, 2015 ; Cai et al, 2021 ). Interestingly, dendritic dystrophy ( Cochran et al, 2014 ; Shi et al, 2020 ) and synapse loss ( Terry et al, 1991 ; Scheff et al, 2007 ) have both been detected in early-stage AD brains and are correlated with cognitive decline. Moreover, Rock2 protein accumulates in the neurons of early-stage human AD brain and remain elevated throughout the disease progression ( Herskowitz et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our initial study, we noticed that a subpopulation of neurons around the sorfra plaques contained heavily labeled sortilin immunoreactive aggregates morphologically resembling the GVD bodies (i.e., Figures 6E1–E3 in Hu et al, 2017 ). During the past few years, we have collected a sufficient number of postmortem brains from youth, adult, and elderly subjects with and without AD-type neuropathology ( Yan et al, 2015 ; Ma et al, 2019 ; Xu et al, 2019 ; Shi et al, 2020 ). In the current study, we carried out correlative pathological characterization and morphometric analyses using temporal lobe sections from selected samples to further understand the development of intraneuronal sortilin aggregation relative to brain aging, sorfra plaque formation, GVD and Tau pathogenesis.…”
Section: Introductionmentioning
confidence: 99%